2009
DOI: 10.1590/s0004-27302009000800017
|View full text |Cite
|
Sign up to set email alerts
|

Total estradiol, rather than testosterone levels, predicts osteoporosis in aging men

Abstract: Objective: To study and establish sex hormone cutoff levels for osteoporosis risk in men over 50 years old. Methods: Case-control study of 216 men > 50 years, 110 with osteoporosis (O) and 106 with normal bone density (C). We measured estradiol (E2), sex hormone binding globulin (SHBG), total testosterone (TT) and albumin. Free testosterone (FT) and bioavailable testosterone (BT) were calculated through Vermeulen's formula. Results: There was no difference in TT between groups. Relative risks of osteoporosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…As we know, hormonal changes are vital factors for osteoporosis development especially in elderly women. There are controversial studies regarding the exact status of this important hormone in osteoporotic patients [56,57]. Nguyen et al showed that the serum levels of estradiol are important for bone mass development in both men and women [23].…”
Section: Discussionmentioning
confidence: 99%
“…As we know, hormonal changes are vital factors for osteoporosis development especially in elderly women. There are controversial studies regarding the exact status of this important hormone in osteoporotic patients [56,57]. Nguyen et al showed that the serum levels of estradiol are important for bone mass development in both men and women [23].…”
Section: Discussionmentioning
confidence: 99%
“…SHBG levels (detectable range: 0.2–180 nmol/L; inter-assay CV of 4.8%, and intra-assay CV of 3.5%) were determined using a DPC Immulite analyzer (Diamond Diagnostics, Holliston, MA). Free E2 was calculated based on mass action laws with Vermeulen's formula [38], [39].…”
Section: Methodsmentioning
confidence: 99%
“…Hypogonadism with low testosterone levels is common in men with osteoporosis and fragility fractures [21]. An 8 am testosterone level and percentage of free testosterone measurement are often added to the osteoporosis workup panel for men.…”
Section: Diagnosis and Treatment Of Diseases Associated With Impairedmentioning
confidence: 99%